2000
DOI: 10.2307/3318671
|View full text |Cite
|
Sign up to set email alerts
|

The Stochastic EM Algorithm: Estimation and Asymptotic Results

Abstract: The EM algorithm (Dempster, Laird, and Rubin (1978)) is a much used tool for maximum likelihood estimation in missing or incomplete data problems. However, calculating the conditional expectation required in the E-step of the algorithm may be infeasible, especially when this expectation is a large sum or a high-dimensional integral. Instead an estimate of the expectation can be formed by simulation. This is the common idea in the stochastic EM algorithm (Celeux and Diebolt (1986)) and the Monte Carlo EM algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
165
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 22 publications
0
165
0
Order By: Relevance
“…The additional variability introduced by sampling in stochastic EM means that it is less likely to get stuck in sub-optimal solutions, although the output of the algorithm is a distribution over hypotheses rather than a single hypothesis. The sequence of hypotheses produced by stochastic EM form a homogeneous Markov chain, and conditions for the ergodicity of this chain have been established (Ip, 1994(Ip, , 2002Diebolt & Ip, 1996;Nielsen, 2000). Empirical and theoretical results indicate that the stationary distribution over hypotheses produced by this Markov chain is approximately centered on the maximum-likelihood solution, with a variance that increases as a function of the rate at which the hypotheses change across iterations (Celeux & Diebolt, 1985, 1988Celeux, Chauveau, & Diebolt, 1995;Diebolt & Ip, 1996;Ip, 1994;Nielsen, 2000).…”
Section: Iterated Learning By Map Estimation and The Stochastic Em Almentioning
confidence: 99%
See 1 more Smart Citation
“…The additional variability introduced by sampling in stochastic EM means that it is less likely to get stuck in sub-optimal solutions, although the output of the algorithm is a distribution over hypotheses rather than a single hypothesis. The sequence of hypotheses produced by stochastic EM form a homogeneous Markov chain, and conditions for the ergodicity of this chain have been established (Ip, 1994(Ip, , 2002Diebolt & Ip, 1996;Nielsen, 2000). Empirical and theoretical results indicate that the stationary distribution over hypotheses produced by this Markov chain is approximately centered on the maximum-likelihood solution, with a variance that increases as a function of the rate at which the hypotheses change across iterations (Celeux & Diebolt, 1985, 1988Celeux, Chauveau, & Diebolt, 1995;Diebolt & Ip, 1996;Ip, 1994;Nielsen, 2000).…”
Section: Iterated Learning By Map Estimation and The Stochastic Em Almentioning
confidence: 99%
“…The sequence of hypotheses produced by stochastic EM form a homogeneous Markov chain, and conditions for the ergodicity of this chain have been established (Ip, 1994(Ip, , 2002Diebolt & Ip, 1996;Nielsen, 2000). Empirical and theoretical results indicate that the stationary distribution over hypotheses produced by this Markov chain is approximately centered on the maximum-likelihood solution, with a variance that increases as a function of the rate at which the hypotheses change across iterations (Celeux & Diebolt, 1985, 1988Celeux, Chauveau, & Diebolt, 1995;Diebolt & Ip, 1996;Ip, 1994;Nielsen, 2000). A more precise characterization of the consequences of stochastic EM can be given in special cases, such as estimating parameters for the kind of clustering problem introduced above (Diebolt & Celeux, 1993;Nielsen, 2000), but there are no explicit results characterizing the asymptotic behavior of stochastic EM when the set of hypotheses is discrete.…”
Section: Iterated Learning By Map Estimation and The Stochastic Em Almentioning
confidence: 99%
“…Wei & Tanner (1990) showed that MCMC simulation can be used to make the E step more practical. A number of similar approaches for the use of MCMC in the EM algorithm have been tested and found workable for particular classes of problems (Geyer, 1992a;Nielsen, 2000;Jank & Booth, 2003;Caffo et al, 2005;Marschner, 2001;Valpine, 2003). Second, very recent publications indicate that MCMC calculations can be used to derive ML estimates.…”
Section: Optimization: Simulated Annealingmentioning
confidence: 99%
“…The sequence of parameter estimates converges to an ergodic Markov Chain in the limit. Following Nielsen (2000aNielsen ( , 2000b we characterize the asymptotic distribution of our sequential method-ofmoments estimators based on M imputations. A difference with most applications of EMtype algorithms is that we do not update parameters in each iteration using maximum likelihood, but using quantile regressions.…”
Section: Introductionmentioning
confidence: 99%